Perception of Ethical Considerations in Social and Humanistic Research: A Study with Scholars of Banaras Hindu University - Mukherjee, Bhaskar (DESIDOC Journal of Library & Information Technology, 2025)
Perception of ethical issues in academic and professional environment has become extremely essential with the increasing instances of misconduct in research. The present study tests the perception level of research scholars in the disciplines of social sciences and arts & humanities of Banaras Hindu University, Varanasi on various issues on research ethics. An open-ended questionnaire was distributed and 332 responses received from the scholars have been used for analysis. The results show researchers still perceived honesty (23 %), integrity/ dignity (18 %), responsible publication (10 %) as the top three issues under research ethics. There was lack of awareness on ethical issues like openness, informed consent, accountability etc. Scholars of social sciences and humanities are not well accustomed with existing ethical guidelines and they breach ethical norms. Despite several earlier studies mentioned that use of AI in research generate closely resemble existing research, therefore lacks transparency, non-neutral, hallucinated results, at least 34 % respondents are using/have used ChatGPT in research, mostly for academic writings followed by review of literature. Almost 36 % scholars have agreed that either they or their fellow researchers engaged in the data falsification, fabrication or manipulation in research, in spite, 52 % researchers believe in maintaining honesty, fairness and integrity in research is necessary. This research recommends the constitution of research ethics monitoring committee at university level to serve as a gatekeeper on the issues like informed consent, covert research, potentially sensitive topics, conflict of region, vulnerable participants.